2010
DOI: 10.1093/cvr/cvq189
|View full text |Cite
|
Sign up to set email alerts
|

Cell line-dependent differentiation of induced pluripotent stem cells into cardiomyocytes in mice

Abstract: Mouse iPS cells differentiate into cardiomyocytes in a cell line-dependent manner. TSA induces myocardial differentiation in mouse iPS cells and might be useful to overcome cell line variation in the differentiation efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 25 publications
2
51
1
2
Order By: Relevance
“…Previous studies have revealed that the expression of four transcription factors [octamer-binding transcription factor 4 (Oct4), sex determining region Y-box 2 (SOX2), avian myelocytomatosis viral oncogene homolog (c-Myc) and Krüppel-like factor 4 (KLF4)] is sufficient to reprogram differentiated cells to pluripotency (4,5). SOX2 and Oct4 are important for maintaining self-renewal and pluripotency in pluripotent stem cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the expression of four transcription factors [octamer-binding transcription factor 4 (Oct4), sex determining region Y-box 2 (SOX2), avian myelocytomatosis viral oncogene homolog (c-Myc) and Krüppel-like factor 4 (KLF4)] is sufficient to reprogram differentiated cells to pluripotency (4,5). SOX2 and Oct4 are important for maintaining self-renewal and pluripotency in pluripotent stem cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cell fate specifi cation and maturation can be selectively altered via manipulation of endogenous developmental signaling pathways (Rathjen and Rathjen 2003 ;Meyer et al 2009 ) . The ability to differentiate iPS cells in vitro to specifi c lineages effi ciently and reproducibly has been achieved using those described protocols with certain modifi cations (Dimos et al 2008 ;Narazaki et al 2008 ;Tateishi et al 2008 ;Wernig et al 2008 ;Ebert et al 2009 ;Hu and Zhang 2009 ;Jin et al 2009 ;Karumbayaram et al 2009 ;Pfannkuche et al 2009 ;Senju et al 2009 ;Tanaka et al 2009 ;Taura et al 2009b ;Zhang et al 2009b ;Carvajal-Vergara et al 2010 ;Comyn et al 2010 ;Dick et al 2010 ;Gamm and Meyer 2010 ;Huang et al 2010 ;Kaichi et al 2010 ;Lamba et al 2010 ;Lee et al 2010 ;Martinez-Fernandez et al 2010 ;Parameswaran et al 2010 ;Swistowski et al 2010 ;Teramura et al 2010 ;Zhou et al 2010 ) .…”
Section: Differentiation Of Obtained Ips Cells To Desired Cell Typesmentioning
confidence: 99%
“…Examples are auditory retinal cells (Jin et al 2009 ;Comyn et al 2010 ;Lamba et al 2010 ;Parameswaran et al 2010 ) , cardiomyocytes (Narazaki et al 2008 ;Pfannkuche et al 2009 ;Tanaka et al 2009 ;Zhang et al 2009b ;CarvajalVergara et al 2010 ;Kaichi et al 2010 ;Martinez-Fernandez et al 2010 ) , insulinsecreting islet-like clusters (Tateishi et al 2008 ) , motor neurons (Dimos et al 2008 ;Ebert et al 2009 ;Hu and Zhang 2009 ;Karumbayaram et al 2009 ) , dopaminergic neurons (Wernig et al 2008 ;Cai et al 2010 ;Swistowski et al 2010 ) , auditory spinal ganglion neurons (Nishimura et al 2009 ) , smooth muscle cells (Taura et al 2009b ;Xie et al 2009 ) , vascular endothelial cells (Taura et al 2009b ) , dendritic cells and macrophages (Senju et al 2009(Senju et al , 2010 , adipocytes (Tashiro et al 2009 ;Taura et al 2009a ) , osteoblasts (Tashiro et al 2009 ) , hematopoietic cells (Hanna et al 2007 ;Eminli et al 2009 ;Kaufman 2009 ;Lu et al 2009 ;Okabe et al 2009 ;Raya et al 2009 ;Kaneko et al 2010 ) , and endothelial progenitor cells (Xu et al 2009 ;Abaci et al 2010 ;…”
Section: Differentiation Of Obtained Ips Cells To Desired Cell Typesmentioning
confidence: 99%
“…However, it is unknown whether iPSC can differentiate into cardiomyocytes without EBs formation and without using collagen IV-coated dishes or feeder cells. In addition, myocardial cell differentiation efficiency has still not been determined as being uniform or diverse in different iPS cell lines (Kaichi et al, 2010). The transcription factors, such as GATA4 and Nkx2.5, expressed in the lateral mesoderm play important roles in the following heart developmental processes (Molkentin et al, 1997;Kasahara et al, 1998).…”
Section: Applications In Organogenesis and Target Organ Toxicity Testingmentioning
confidence: 99%